Exploring network structure and the role of key stakeholders to understand the obesity prevention system in an Australian metropolitan health service: Study protocol - Jancey, Jonine; Leavy, Justine; Pollard, Christina; Szybiak, Maria; Blackford, Krysten; Riley, T.; Milligan, M.; Chamberlain, D. (2019)
Introduction: Little progress has been made to address the increasing obesity prevalence over the past few decades, and there is growing concern about the far-reaching consequences for health and well-being related to obesity on a global scale. Systems thinking is emerging as a suitable approach for obesity prevention, as it allows health researchers, practitioners and policy-makers to systematically synthesise existing data, expose gaps, inform priority setting and identify leverage points in the system. The aim of this study is to trial a systems thinking approach to better understand the local obesity prevention system, and identify gaps and viable opportunities for health promotion activities to strengthen obesity prevention efforts in an Australian metropolitan health service. Methods and analysis: A mixed methods design will be undertaken in a metropolitan health service area in Perth, Western Australia in 2019-2020. A systems inventory audit will be used to identify physical activity, nutrition and overweight/obesity prevention activities taking place in the study area. An organisational network survey will be administered, and a social network analysis undertaken to examine relationships between organisations in the network. The relationships and interactions will compare the level and type of interactions each organisation has within the network. Parameters including density, centrality and betweenness will be computed using UCINET and Netdraw. Ethics and dissemination: Ethics approval has been obtained from the Curtin University Human Research Ethics Committee (approval number HRE2017-0862). Results will be reviewed with members of the advisory group, submitted to relevant journals and presented at relevant conferences to health promotion practitioners and policy-makers. The area health service, as co-producers of the research, will use findings to inform policy and strategy across the study area.